Effect of 360° TitaniUM Core Strength Exercise© on pain intensity and trunk extensor performance amongst chronic non-specific low back pain in Malaysian government sector workers - Lai, Ling Ling; Chee, Chen Soon; Samsudin, Shamsulariffin; Lim, Boon Hooi (Pakistan Cardiac Society, 2023)
This preliminary study aimed to assess the effectiveness of the 360° TitaniUM Core Strength Exercise© on both pain intensity and trunk extensor performance amongst chronic non-specific low back pain (NSLBP) in Malaysian government sector workers. Participants with chronic NSLBP were randomly assigned into either the interventions or control group. Participants in the intervention groups received a 12-week program of the 360° TitaniUM Core Strength Exercise© with progressively increased on the frequency, intensity, or duration of training, while the control group received no treatment. Pain intensity and trunk extensor performance were assessed at pre-intervention and post-intervention. The results showed a significant improvement in pain intensity and trunk extensor performance in all intervention groups compared to the control group, with the intervention duration group and intervention intensity group indicated a superior improvement, respectively. Although the intervention groups experienced a great reduction in pain intensity, no statistically significant difference was observed between all groups. Whereas there was a significant interaction between time and groups on trunk extensor performance between all the interventions and control group. These findings suggest that the 360° TitaniUM Core Strength Exercise© with appropriate dosage of exercise is an effective core exercise program for managing chronic NSLBP.